Thoracoscopy for Esophageal Diverticula After Esophageal Atresia With Tracheo-Esophageal Fistula - Yong, Zhao; Dingding, Wang; Kaiyun, Hua; Yichao, Gu; Yanan, Zhang; Junmin, Liao; Shen, Yang; Shuangshuang, Li; Peize, Wang; Jinshi, Huang (Frontiers in Pediatrics, 2021)
Background: Esophageal diverticulum (ED) is an extremely rare complication of congenital esophageal atresia (EA) with or without tracheoesophageal fistula (TEF) surgery. We aimed to investigate feasible methods for the treatment of this rare complication. Methods: We retrospectively reviewed all patients with EA/TEF at Beijing Children's Hospital from January 2015 to September 2019. The clinicopathological features of patients with ED after EA/TEF surgery were recorded. Follow-up was routinely performed after surgery until December 2020. Results: Among 198 patients with EA/TEF, ED only occurred in four patients (2.02%; one male, three female). The four patients had varying complications after the initial operation, including anastomotic leakage (3/4), esophageal stenosis (3/4), and recurrence of TEF (1/4). The main clinical symptoms of ED included recurrent pneumonia (4/4), coughing (4/4), and dysphagia (3/4). All ED cases occurred near the esophageal anastomosis. Patients’ age at the time of diverticulum repair was 6.6–16.8 months. All patients underwent thoracoscopic esophageal diverticulectomy (operation time: 1.5–3.5 h). Anastomotic leakage occurred in one patient and spontaneously healed after 2 weeks. The other three patients had no peri-operative complications. All patients were routinely followed up after surgery for 14–36 months. During the follow-up period, all patients could eat orally, had good growth and weight gain, and showed no ED recurrence or anastomotic leakage on esophagogram. Conclusions: ED is a rare complication after EA/TEF surgery and is a clear indication for diverticulectomy. During the midterm follow-up, thoracoscopic esophageal diverticulectomy was safe and effective for ED after EA/TEF surgery.